THE EFFECT OF ANXIETY ON THE PSYCHOLOGICAL WELFARE OF EMPLOYEES IN THE COVID-19 PANDEMIC - Dian Novita Siswanti; Nur Afni Indahari; Novita Maulidya Jalal; Rusli (European Journal of Research Development and Sustainability, 2022)
The purpose of this study was to describe the psychological well-being of employees during the COVID-19 pandemic. The research method used was descriptive quantitative method. The population in this study were employees of Bumi Sarana Utama (BSU) at PT Hadji Kalla Makassar. The sampling technique used a purposive sampling technique, namely the sample had been appointed and recommended directly by PT Hadji Kalla Makassar as many as 221 people. The data collection technique used the SRQ-anxiety scale. 20 and psychological well-being questionnaire through google form. The data analysis technique used was simple regression analysis. The results showed that the significance value was 0.0151 (p>0.05), which means the null hypothesis is accepted, that is, there is no influence of anxiety on the psychological well-being of employees during the COVID-19 pandemic